2021
DOI: 10.1088/1748-9326/abde05
|View full text |Cite
|
Sign up to set email alerts
|

The driving forces behind the change in energy consumption in developing countries

Abstract: Economic growth is principally powered by energy fuels. While the potential energy transition pathways in developed countries are clear, they have not been well explored for developing countries. Here, we study the average annual growth rate of energy consumption in 12 aggregated regions during 2001–2017 and the driving factors behind that growth. The countries with high energy consumption growth rates were concentrated in Asia and North Africa and four of the top five regions were in Asia, while the energy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The rate of emissions from energy consumption by agricultural operations has increased more rapidly in developing countries than that of developed countries. This is due to the greater reliance on fossils fuels, notably coal, oil, and natural gas in developing countries and the increased shift towards low-emissions and renewable energy sources (e.g., hydro, solar, wind, and bioenergy) in developed countries [ 66 , 67 ]. Several studies have found that the adoption of low-emissions energy technologies, renewable energy, and energy-efficient management practices in agriculture has the potential to reduce GHG emissions caused by energy consumption in developing countries [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The rate of emissions from energy consumption by agricultural operations has increased more rapidly in developing countries than that of developed countries. This is due to the greater reliance on fossils fuels, notably coal, oil, and natural gas in developing countries and the increased shift towards low-emissions and renewable energy sources (e.g., hydro, solar, wind, and bioenergy) in developed countries [ 66 , 67 ]. Several studies have found that the adoption of low-emissions energy technologies, renewable energy, and energy-efficient management practices in agriculture has the potential to reduce GHG emissions caused by energy consumption in developing countries [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…In SSA, each year over half a million premature deaths are linked to indoor air pollution caused by cooking with fossil fuels and woodfuel (IEA 2017). Other deaths, though not officially accounted for, may be attributed to under-nutrition resulting from women and children walking long distances to collect firewood (Li et al 2021).…”
Section: Sustainable Utilization In Cooking Systemsmentioning
confidence: 99%
“…Woodfuel is preferred for its affordability, accessibility, and compatibility with cooking culture, including availability in the form and amounts required. Inefficient production and use results in diverse negative environmental and health impacts, including degradation of woodlands and severe and chronic respiratory problems (Li et al 2021). These negative impacts have resulted in efforts to shift from woodfuel to other forms of cooking energy with a noble aim of addressing the adverse implications associated with its use.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of electricity has led to more primary fuels (especially coals) being burned in the energy sector. The occurrence of environmental disasters and concerns on human health , promotes switching from dirty solid fuels to clean modern energies such as natural gas and biogas in many developing countries. , Usually, the combustion of fossil fuels such as coals and petroleum oils is believed to be the main source of ambient CO 2 causing global warming. International Energy Agency (IEA) estimated that energy-related CO 2 emission was 36.3 Gt in 2021, with nearly 92.3% (33.5 Gt) from fossil fuel combustion …”
Section: Introductionmentioning
confidence: 99%